The ineffectiveness of Peruvian language policies: A case study on the violation of the rights of indigenous populations - Ayala Nagao, Daryl Bridget Valerie (2021)
In Peru, language policies include a set of regulations that ensure the use and maintenance of the different languages spoken in its territory. However, these legal frameworks are not effectively enforced and are transgressed. For this reason, three cases of violation of the rights of indigenous populations were selected, in which the existence of factors that cause the ineffectiveness of language policies in Peru is proposed. These files were collected from online government repositories and examined from an analytical-descriptive perspective. Finally, the review of the data revealed the existence of practices that marginalize indigenous communities based on the ideology of a hegemonic language, which leads to centralized public policies, invisibilization of indigenous populations and non-compliance with laws benefiting native languages